Transcriptional profile of Glaesserella parasuis in swine serosal and joint fluids - Nielsen, Daniel W.; Sarlo Davila, Kaitlyn M.; Brockmeier, Susan L.; Hau, Samantha J. (Frontiers in Veterinary Science, 2025)
Glaesserella parasuis is the causative agent of Glässer's disease and contributes to significant post-weaning mortality in the swine industry. Glässer's disease is characterized by meningitis, polyserositis, and polyarthritis. Previous work has examined transcriptomic differences of G. parasuis when inoculated into different in vitro conditions, lung explants, or the lung in vivo following intratracheal challenge. However, it is still unknown how the transcriptome of G. parasuis may change to cause polyserositis or polyarthritis. Here, we incubated G. parasuis in acellular joint or serosal fluid for 3 and 12 hours to better understand transcriptional changes in the joint or serosal compartment. When G. parasuis serovar 5 strain 29755 was incubated in host fluid for 3h, cell wall, membrane, and envelope biogenesis genes were downregulated compared to G. parasuis incubated in PBS. In contrast, translation, ribosomal structure, and biogenesis and carbohydrate transport and metabolism were upregulated in the host fluid compared to PBS. Additionally, there were eleven differentially expressed genes with an unknown function shared between the acellular joint and serosal fluid at the 3h timepoint compared to PBS. When comparing the differences between the host fluids from 12 to 3h and the host fluids at 3h compared to PBS, this study found sixteen genes with inverse expression patterns. An investigation into the hypothetical genes identified and the nineteen shared genes in all comparisons may provide further knowledge about the pathogenesis of G. parasuis, which may be useful in developing interventions against Glässer's disease.